Results of treating primary tumours of the trachea by irradiation. - Rostom, A Y (1978)
Forty-four patients presented with primary tumours of the trachea over a 25-year period. Thirty-nine of them were treated by irradiation. Of these, 24 (61.5%) died as a result of their disease while 30% are either alive and well (4.4-11 years) or have died of intercurrent disease (average four years). Recurrences or metastases when they occurred were in the first two years after diagnosis in all but one patient, who developed local recurrence 3.25 years later. Three patients died of unknown cause (average 5.6 years) after irradiation. Two factors seem to determine the prognosis: the histology and the extent of disease on presentation. Dysphagia without oesophageal involvement carried a grave prognosis.